Inteligência coletiva e democracia : um modelo teórico para analisar crowdlaw aplicado a processos participativos de seis países - Marco Antonio Konopacki (2021)
Crowdlaw in participatory studies emerged at the conference organized by The Governance Lab, in 2014, to discuss new forms of participation through digital technologies. Authors who work with the term propose tap the collective intelligence, mediated by digital tools, into policymaking. The innovations proposed by crowdlaw, however, are claimed more from narratives of empirical studies than the dialogue with other works of democratic theory and digital democracy. Due to the limited offer of theoretical papers on the subject, crowdlaw has not established itself as a concept capable of dialoguing with other fields of studies on public participation and deliberation, despite its potential to mobilize different theoretical frameworks in the field. This dissertation makes a theoretical approach, seeking to locate crowdlaw in participatory and deliberative studies and establishes four basic assumptions for analyzing crowdlaw initiatives. This approach takes place in dialogue with specific concepts arising from the application of technology in social and political processes, especially regarding the possibility of having a collective intelligence capable of producing epistemic gains on democratic decisions. The final product presented by this dissertation is a redefinition of crowdlaw as an agenda for the State transformation that lays in four theoretical assumptions. The analysis of cases based on a theoretical model built for this dissertation, establishes a qualitative analysis framework to asses the adherence of the initiatives to crowdlaw.